Tingkat profitabilitas pembiayaan mikro dan metode economic value added : studi pada bank bri syariah - Al Arif, M Nur Rianto; Hanifa, Suci (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2017)
Microfinance is one of the Islamic bankâ€™s products for micro, small, and medium enterprises. The aim of this research is to analyze the profitability ratio in micro finance using economic value added method. The object of this study is at Bank of BRI Sharia. The result show that in 2014 had an economic value addedÂ (EVA)about Rp 327.030.746.600 or about 10,48% from the financing. The EVAâ€™s value shows that the microfinance at Bank of BRI Sharia had good enough. The implication of this result is Bamk of BRI Sharia should maintance and increase the quality of the financing strategy in microfinance product.